2016
DOI: 10.18632/oncotarget.14136
|View full text |Cite
|
Sign up to set email alerts
|

Low lymphocyte-to-white blood cell ratio and high monocyte-to-white blood cell ratio predict poor prognosis in gastric cancer

Abstract: Previous results regarding the prognostic value of the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in gastric cancer are conflicting, and full analysis of other blood test parameters are lacking. We therefore examined the associations between various blood test parameters and prognosis in 3243 gastric cancer patients randomly divided into training (n=1621) and validation (n=1622) sets. Optimal cut-off values of 0.663 for neutrophil-to-white blood cell ratio (NWR), 0.288 for lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 31 publications
(34 reference statements)
5
40
0
Order By: Relevance
“…Therefore, irradiation to the normal liver using the TomoHelical mode might lead to increases in TGF‐β1 and Treg number, decreasing the efficacy of DC‐based vaccine therapy. It was reported that the pretreatment NLR, MLR, and PLR were associated with the prognosis of patients with malignant solid tumors . In a systematic review and meta‐analysis, NLR greater than 4 was associated with the poor prognosis, and this was also the case in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, irradiation to the normal liver using the TomoHelical mode might lead to increases in TGF‐β1 and Treg number, decreasing the efficacy of DC‐based vaccine therapy. It was reported that the pretreatment NLR, MLR, and PLR were associated with the prognosis of patients with malignant solid tumors . In a systematic review and meta‐analysis, NLR greater than 4 was associated with the poor prognosis, and this was also the case in our study.…”
Section: Discussionsupporting
confidence: 84%
“…At the time of diagnosis and treatment, peripheral blood tests can reflect the tumor inflammatory conditions. The peripheral blood parameters, including white blood cell, neutrophil, lymphocyte, monocyte, and platelet counts, as well as the neutrophil-to-lymphocyte ratio (NLR), derived NLR (d-NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR), are the systemic inflammatory response indicators that have been widely proposed as prognostic factors for many malignancies 18,19…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, high NLR, high PLR, high monocyte to lymphocyte ratio, high neutrophil to white cell ratio, low lymphocyte to white cell ratio (LWR) were associated with survival in univariate analysis, but only low LWR and high MWR were independent prognostic factors for poor survival [90].…”
Section: Peripheral Blood Monocytes In Gastric Cancer Assessmentmentioning
confidence: 86%